Ho Chi Minh’s thought on building a new life for youth - Nguyễn Thị Hiếu (Tạp chí Nghiên cứu Khoa học Công đoàn, 2022)
Ho Chi Minh’s thought is a science, based on Marxism-Leninism and becoming a torch to guide the revolution of Vietnam. In particular, President Ho Chi Minh pays special attention to building a new lifestyle for youth. His views on building new lifestyles for young people are always valuable, practical and theoretical.